Foreign language learning in the Early Years in the Madrid Region: teachers’ profile, perceptions and methodologies - Fleta Guillén, M. Teresa (Didáctica. Lengua y Literatura, 2016)
This article focuses on the beliefs, perceptions and practices of foreign language practitioners in Pre-school Education in the Madrid Region. With information from the current regulations and with data from a study conducted in public and private schools, the article analyzes the methodologies, perceptions and different types of teachers’ profile, reflecting on the need to rethink the training system in order to adapt it to the requirements of the current educational situation of bilingual education. The conclusions and implications focus on a set of considerations for tailoring the methodologies and the role of the pre-and in-service teacher training to the implementation of the early foreign language education policy in the region.